7 Comparison of Efficacy and Safety of a Dipigmented Polymerized Allergen Extract of Grass and Birch with Placebo in Patients With Type-1 Allergic Rhinoconjunctivitis - Sager, Angelika (World Allergy Organization Journal, 2012)
BACKGROUND: The safety and efficacy of specific immunotherapy (SIT) with depigmented and polymerized allergen extracts of pollen is well documented in several clinical trials. We investigated efficacy and safety of an extract containing 2 taxonomically non-related pollen species (birch and grasses) in a subcutaneous immunotherapy over 2 pollen seasons in co-sensitized allergic patients with rhinitis and/or rhinoconjunctivitis with or without allergic asthma. METHODS: 269 (ITT) patients with confirmed rhinitis and/or rhinoconjunctivitis were treated during 2009 and 2010 in Germany, Romania, Poland, Lithuania, and Bulgaria. For each patient a 1-day build-up phase applying 0.2 mL and 0.3 mL of 1000 DPP/mL allergen extract was applied. During the remaining 18-month period maintenance 500 DPP were administered in 4 to 6 weeks intervals. Patients were randomised to the treatment groups on a 2:1 basis (175 verum: 94 placebo). The main parameter in this study was the combined symptom and medication score during the birch and grass pollen season 2010 over 7 weeks. Secondary parameters were symptom score, medication score, IgE, IgG4 as well as quality of life. RESULTS: During the 2010 season a statistically significant difference (P = 0.0385) was observed between treatment groups: in patients treated with the allergen extract the median time weighted AUC of the combined symptom and medication score was 5.70, in patients treated with placebo 7.07. This effect was predominantly due to the reduction of symptom score by 21% over placebo. The intake of recue medication was very low during both seasons leading only to a 10% reduction (ns). Birch and phleum specific IgE did not change during the course of the study in both groups whereas respective IgG4 levels increased only in the verum group and remained nearly unchanged in the placebo group (P < 0.0001). Total QoL score was improved in verum patients (P = 0.0254). 5.4% of the patients in the verum group and 4.0% of the patients in the placebo group developed mild systemic reactions. CONCLUSIONS: The results show that specific immunotherapy with a depigmented polymerized extract of 2 taxonomically non-related pollen (birch and grass) was effective and safe demonstrated by clinical and immunological parameter.